A tecnologia educativa no currículo escolar e na formação docente no Chile - Duran, Maria Renata; Bueno, Belmira; Schalck, Ana Elena (Diálogos Latinoamericanos, 2014)
The association of the use of digital information and communication technologies (TDIC) and improve professional performance has been widespread in various countries and justified the use of such technological devices in schools and certain curricular changes. In Latin America, Chile is an exemplary case of this policy. Considering the importance of this issue for the Brazilian context, with a view to discussing TDIC in schools, this article aims to analyze the relations between technologies and teaching digital literacy. It presents an analysis of the insertion of the discipline of Educational Technology in the curriculum of Chilean schools in the 1996-2002 period, based on documents and literature search and an interview. The focus is on policies concerning the use of TDIC in teacher training, especially the Enlaces program.